Kontribusi Dukungan Orangtua, Teman Sebaya, dan Guru Bimbingan dan Konseling terhadap Minat Siswa pada Jurusan yang Ditempati di SMA - Rika Devianti (Jurnal Konseling dan Pendidikan, 2015)
SMA Negeri 1 Reteh has two departments: IPA and IPS. Majors placement is an effort so that all students can develop their knowledge and skill,  accordance with their potential and interests. Students who take unsuitable courses with their potential and interests, will have a lot of problems in learning. Interest in their department can be influenced by parent, peer, and counselor. The purpose of this research is to describe and  determine the contribution a parent support, peer, and counselor to the occupied student’s interest. This study uses a quantitative approach with a descriptive correlational method. The population in this study were students of class X and XI, the technique used purposive sampling. The instrument used a questionnaire with Likert scale. The results of the parent-support reliability test is 0.922, peer  is 0.908, counselor is 0.906, and the interest of students in the occupied department is 0.944. The data were analyzed using multiple regression. The findings of this study indicate that the results description support of parent, peer, and counselor individually or together to the student's interest in the occupied department in high category and results hypothesis the support of parent, peer, and counselor individually or together contribute to the student's interest in the occupied department.